Innovative Ethno-Realistic Mathematics-based modules: Promoting Pancasila values in Indonesian mathematics education - Pujiastuti, Nur Ika; Prahmana, Rully Charitas Indra; Evans, Brian (Mathematics Education Journal, 2025)
The teaching of mathematics in Indonesia faces notable challenges, particularly in effectively conveying mathematical concepts to students. This has created a need for instructional modules that provide better support for learners. Current modules, however, do not adequately incorporate the Pancasila Students Profile (PSP), especially in terms of fostering critical reasoning skills. Therefore, there is an urgent demand for alternative instructional materials based on the Ethno-Realistic Mathematics Education (Ethno-RME) approach, which aligns with the competencies outlined in the PSP—a framework grounded in the nation's foundational values—and connects learning with students' daily experiences. This study aims to develop an Ethno-RME-based module that is valid, practical, and effective in enhancing students' critical reasoning abilities. The research adopts a design research methodology of the development studies type, structured into two key phases: preliminary and formative evaluation. Data collection methods included the use of assessment sheets, walkthroughs, document analysis, and tests of students' critical reasoning skills. The study was conducted with 22 eighth-grade students at a private secondary school in Yogyakarta. The results indicate that the Ethno-RME-based module is both valid and practical, with promising potential to improve students' critical reasoning. Specifically, the module received high validity ratings, with the material scoring an average of 165 out of 175 and the media quality receiving 129 out of 135. The one-to-one evaluation phase produced an average score of 74 out of 75. During the small group trial, the module achieved an average student response score of 66.33 out of 75, and in the field test stage, it scored an average of 64.45 out of 75, confirming its practicality. Furthermore, the second stage of the field test revealed a positive effect on critical reasoning. These findings demonstrate the efficacy of the Ethno-RME-based module in enhancing the critical reasoning skills of students in accordance with the Pancasila Student Profile.